From transference to creativity. The cultural roles of science in developing countries (Polis (Santiago), 2018)
The author claims that science and technology are now two powerful international social and cultural institutions that aim to produce valid knowledge and products for global consumption. From this, questions the assumption that culture is a separate sphere and secondary, merely superstructural. And argues that culture is the environment in which ideas are produced by which we live our lives and that they penetrate science. Given the culture condition of science, that allows to state that to become scientifically developed may not necessarily mean becoming like Europe and/or the United States. After that he asks for the features that should have  technology in Latin America.
Keywords: science; technology; world consumption; development; Latin America